2008
DOI: 10.1002/erv.866
|View full text |Cite
|
Sign up to set email alerts
|

Using neuropsychological feedback therapeutically in treatment for anorexia nervosa: two illustrative case reports

Abstract: Information processing in anorexia nervosa (AN) has been characterised as having a tendency to get trapped in detail, and having difficulties with set-shifting. These characteristics can be addressed in treatment through personalised interventions targeting thinking styles and their role in the development and maintenance of an eating disorder (ED). This paper outlines a three-session assessment and feedback module designed to identify and address these information processing biases. Two case reports are prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…Our results showed primary SIP along with working-memory and inhibition=impulsivity impairments unrelated to BMI, which affect and worsen both primary visual and verbal memory abilities during the course of the illness. As cognitive rehabilitation has proven effective for improving cognitive abilities, the clinical implications of our results suggest that interventions must include executive functioning (cognitive flexibility, inhibition=impulsivity; Tchanturia et al, 2008), speed and style of information processing (Lopez, Roberts, Tchanturia, & Treasure, 2008), and visual memory as targets to generalize improvements to other cognitive abilities such as verbal memory.…”
Section: Emotional Variablesmentioning
confidence: 90%
See 1 more Smart Citation
“…Our results showed primary SIP along with working-memory and inhibition=impulsivity impairments unrelated to BMI, which affect and worsen both primary visual and verbal memory abilities during the course of the illness. As cognitive rehabilitation has proven effective for improving cognitive abilities, the clinical implications of our results suggest that interventions must include executive functioning (cognitive flexibility, inhibition=impulsivity; Tchanturia et al, 2008), speed and style of information processing (Lopez, Roberts, Tchanturia, & Treasure, 2008), and visual memory as targets to generalize improvements to other cognitive abilities such as verbal memory.…”
Section: Emotional Variablesmentioning
confidence: 90%
“…Tchanturia et al (2008) demonstrated improvements on neuropsychological tests after 10 sessions of cognitive remediation therapy including exercises focused on cognitive flexibility as set shifting has been found impaired in AN (Holliday et al, 2005;McAnarney et al, 2011;Stedal, Rose, Frampton, Landro, & Lask, 2012). Lopez, Roberts, Tchanturia, and Treasure (2008) demonstrated clinical improvements after only 3 sessions of cognitive intervention using neuropsychological feedback. Regarding inhibition, our results support the findings reported by Stedal et al (2012) as worse performance was found in the interference part within the Stroop test.…”
Section: Executive Functioningmentioning
confidence: 99%
“…Details of the adaptations of a motivational approach to EDs and empirical findings supporting this can be found in Treasure and . Feedback about medical risk and "thinking style" based on neuropsychological findings is used to increase motivation to change (Lopez, Roberts, Tchanturia, & Treasure, 2008;Musiat, Hoffmann, & Schmidt, 2012) and to provide the patient with arguments for change. The principles of behavioral change are used to guide people toward recovery (Abraham & Mitchie, 2008;National Institute for Health and Clinical Excellence, 2007).…”
Section: Therapeutic Style Of Mantramentioning
confidence: 99%
“…The potential bearing of this is that at least part of individuals with AN would benefit from treatment that attends to neuropsychological vulnerabilities, such as neuropsychological feedback 44 or mindfulness-based approaches. 1 Indeed, neuropsychological functioning has been found to predict outcome, for example, in terms of weight maintenance after treatment.…”
Section: 17mentioning
confidence: 99%